The practicality of different eGFR equations in centenarians and near-centenarians: which equation should we choose? - Qiuxia Han; Dong Zhang; Yali Zhao; Liang Liu; Jing Li; Fu Zhang; Fuxin Luan; Jiayu Duan; Zhangsuo Liu; Guangyan Cai; Xiangmei Chen; Hanyu Zhu (PeerJ, 2020)
Background No studies have examined the practicality of the Modification of Diet in Renal Disease (MDRD), Chronic Kidney Disease Epidemiological Collaboration (CKD-EPI) and Berlin Initiative Study 1 (BIS1) equations for the estimated glomerular filtration rate (eGFR) in a large sample of centenarians. We aim to investigate the differences among the equations and suggest the most suitable equation for centenarians and near-centenarians. Methods A total of 966 centenarians and 787 near-centenarians were enrolled, and the eGFR was calculated using the three equations mentioned above. Agreement among the equations was investigated with the κ statistic and Bland–Altman plots. Sources of discrepancy were investigated using a partial correlation analysis. Results The three equations for assessing eGFR are not considered interchangeable in centenarians and near-centenarians. Δ(MDRD, CKD-EPI) and Δ(MDRD, BIS1) increased with age, but Δ(CKD-EPI, BIS1) was relatively stable with age. Δ(MDRD, CKD-EPI) and Δ(MDRD, BIS1) were considerable in subjects with Scr levels less than 0.7 mg/dL and decreased with the Scr level. A considerable difference between CKD-EPI and BIS1 was observed for participants with Scr levels ranging from 0.5 to 1.5 mg/dL. This difference increased with Scr levels ranging from 0.5 to 0.7 mg/dL, was relatively stable for Scr levels ranging from 0.7 to 0.9 mg/dL, and decreased with Scr levels ranging from 0.9 to 1.5 mg/dL. The differences in the three comparisons were all greater in women than in men (p < 0.05). Conclusions We tend to suggest the MDRD equation to calculate the glomerular filtration rate (GFR) in elderly individuals >95 years old who have no risk factors for cardiovascular disease; the BIS1 equation to calculate the eGFR for elderly individuals younger than 94 years old who have risk factors for cardiovascular disease; the CKD-EPI equation to calculate the eGFR of elderly individuals with Scr levels greater than 1.5 mg/dL; and the BIS1 equation to calculate the eGFR of older women with Scr levels less than 0.7 mg/dL.